Identification and Characterization of a Brucella abortus ATP-Binding Cassette Transporter Homolog to Rhizobium meliloti ExsA and Its Role in Virulence and Protection in Mice - Rosinha, G. M. S. (American Society for Microbiology, 2002)
Brucella abortus is a facultative intracellular bacterial pathogen that causes abortion in domestic animals and undulant fever in humans. The mechanism of virulence of Brucella spp. is not fully understood yet. Furthermore, genes that allow Brucella to reach the intracellular niche and to interact with host cells need to be identified. Using the genomic survey sequence (GSS) approach, we identified the gene encoding an ATP-binding cassette (ABC) transporter of B. abortus strain S2308. The deduced amino acid sequence encoded by this gene exhibited 69 and 67% identity with the sequences of the ABC transporters encoded by the exsA genes of Rhizobium meliloti and Mesorhizobium loti, respectively. Additionally, B. abortus ExsA, like R. meliloti and M. loti ExsA, possesses ATP-binding motifs and the ABC signature domain features of a typical ABC transporter. Furthermore, ortholog group analysis placed B. abortus ExsA in ortholog group 6 of ABC transporters more likely to be involved in bacterial pathogenesis. In R. meliloti, ExsA is an exopolysaccharide transporter essential for alfalfa root nodule invasion and establishment of infection. To test the role of ExsA in Brucella pathogenesis, an exsA deletion mutant was constructed. Replacement of the wild-type exsA by recombination was demonstrated by Southern blot analysis of Brucella genomic DNA. Decreased survival in mice of the Brucella ΔexsA mutant compared to the survival of parental strain S2308 demonstrated that ExsA is critical for full bacterial virulence. Additionally, the B. abortus exsA deletion mutant was used as a live vaccine. Challenge experiments revealed that the exsA mutant strain induced superior protective immunity in BALB/c mice compared to the protective immunity induced by strain S19 or RB51.